Retrospective 4 : 1979-80 Documents of Artist-Run Centres in Canada. - Manos, Kenna; Mates, Allan; Oppenheimer, Joel; Razutis, Al (Toronto : Annpac, 1981)
Metcalfe, Eric ; Craig, Kate ; Brute, Dr. & Lady ; Conway, Garry ; McKinnon, John ; Peck, Robin ; Prent, Mark ; Savoie, Romeo ; Beesley, Philip ; Greer, John ; Ambroise, Dominique ; Massey, John ; McGee, Chris ; Horne, Stephen ; de Lorenzi, Marie-Josée ; Buff, R.E. ; Schwarz, Judith ; Hill, Peter ; Zednik, Jane ; Kury, Shelly ; Charbonneau, Jacques ; Benner, Ron ; Robinson, Peggy ; Danson, Andrew ; Fernandes, Michael ; Goldberg, Jim ; Meigs, Sandra ; Ontani, Luigi ; Fox, Charlie ; Amundson, Dale ; Wagner, Norma ; Vincent, Bernice ; Zwartsenberg, Annebet ; Nebeska, Eva ; Salzberg, Claire ; Kingma, Corinne ; Donoghue, Lynn ; Gorlitz, Will ; Shapiro, Anita ; Boomen, Anthony Van Den ; Evergon ; Weller, Nina ; Abbott, Louise ; Watkins, Tim ; Hassan, Jamelie ; Tomas, Dave ; Funnell, Suzanne ; Ortiz, Oscar ; Gonzalez, Gildo ; Zingarelli, Lisa ; Maggs, Arnaus ; Butte, Wellington ; Holownia, Thaddeus ; Siegner, Dwight ; Pfliger, T.L. ; Berry, R. ; Joly, François ; Barker, Philip ; Senini, Blake ; Dufour, Gary ; McEwen, John ; Seaward, Diana ; Persson, Per ; Peck, Robin ; Barber, Bruce ; Watt, John ; Ludlow, Greg ; Vincent, Bernice ; Wainio, Carol ; Campbell, Bruce ; Haigh, David ; Fletcher, Kenneth ; Wong, Paul ; Sterbak, Jana ; Wallaca, Gordon ; Beesley, Philip ; Charron, François ; Charney, Sylvia Safdie ; Clark, John ; Carter, Linda ; Wong, Paul ; The Kipper Kids ; Filliou, Robert ; Tourbin, Dennis ; Mischeff, Alezek ; Chitty, Elizabeth ; Horne, Stephen ; McNealy, Robert ; Keetman, Peter ; Tourangeau, Jean ; Lynch, Shaun ; Malis, Viv ; Curmano, Billy ; Research, Fringe ; Wellze, Elzze ; Savoie, Romeo ; Haslam, Prime Beef / Mike ; Purdy, Richard ; Levin, Sandra ; Haslam, Michael ; Kreusen, Jill ; Miller, Roland ; Graff, Tom ; Dance, Terminal City ; etc.
1 catalogus, 150 p. : ill. + 1 bijlage, ongepag. : ill.
You will find, in these pages, a generous sampling of examples of the kind of activity that occurred in Canadian artist-run centres in the 1979-80 season.
Engels & Frans
boek
Keywords: Canada